2011
DOI: 10.1177/00333549111260s311
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Health and Safety in San Francisco's Chinatown Restaurants: Findings and Lessons Learned from a Pilot Observational Checklist

Abstract: Noncompliance with labor and occupational health and safety laws contributes to economic and health inequities. Environmental health agencies are well positioned to monitor workplace conditions in many industries and support enhanced enforcement by responsible regulatory agencies. In collaboration with university and community partners, the San Francisco Department of Public Health used an observational checklist to assess preventable occupational injury hazards and compliance with employee notification requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…26 The partnership evaluation consisted of observations, interviews, and surveys with study partners. 27 Study protocols and data collection instruments were approved by UC Berkeley's Institutional Review Board.…”
Section: The Studymentioning
confidence: 99%
See 4 more Smart Citations
“…26 The partnership evaluation consisted of observations, interviews, and surveys with study partners. 27 Study protocols and data collection instruments were approved by UC Berkeley's Institutional Review Board.…”
Section: The Studymentioning
confidence: 99%
“…Although a detailed presentation of the study findings is beyond the scope of this paper and is available elsewhere, 3,14,[25][26][27] we highlight here those of most relevance to workers, particularly in relation to their primary concerns, wage theft, and other basic worker rights violations. Survey results (n0405) indicated that almost 60 % of participants had experienced wage theft in at least one of its forms.…”
Section: Study Findingsmentioning
confidence: 99%
See 3 more Smart Citations